2023
DOI: 10.3390/catal13060916
|View full text |Cite
|
Sign up to set email alerts
|

Efficient and Stable Ni/SBA-15 Catalyst for Dry Reforming of Methane: Effect of Citric Acid Concentration

Abstract: Citric acid, one of the representative chelate compounds, has been widely used as an additive to achieve the highly dispersed metal-supported catalysts. This study aimed to investigate the effect of citric acid concentration on the preparation of the highly dispersed Ni catalysts on mesoporous silica (SBA-15) for the dry reforming of methane. A series of Ni/SBA-15 catalysts with citric acid were prepared using the acid-assisted incipient wetness impregnation method, and the Ni/SBA-15 catalyst as a reference wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 35 publications
1
4
0
Order By: Relevance
“…All the results were consistent with the previous results of XRD, TEM, and H 2 -TPR results. Moreover, as reported in the literature [40], the Ni/SBA-15 prepared by the acid-assisted co-impregnation method exhibited excellent stability within the testing time of 30 h, which was similar to the results in this work. The conversion of CH 4 and CO 2 in the above-mentioned literature was dependent on the concentration of citric acid used for the preparation of Ni/SBA-15.…”
Section: Catalytic Performance Testssupporting
confidence: 91%
See 1 more Smart Citation
“…All the results were consistent with the previous results of XRD, TEM, and H 2 -TPR results. Moreover, as reported in the literature [40], the Ni/SBA-15 prepared by the acid-assisted co-impregnation method exhibited excellent stability within the testing time of 30 h, which was similar to the results in this work. The conversion of CH 4 and CO 2 in the above-mentioned literature was dependent on the concentration of citric acid used for the preparation of Ni/SBA-15.…”
Section: Catalytic Performance Testssupporting
confidence: 91%
“…The Ni particle size of Ni/SBA-15-M (17.2 nm) was clearly larger than that of Ni/SBA-15-M-C (8.1 nm) and Ni/SBA-15-I (7.8 nm). As reported in the literature [40], Ni/SBA-15 catalysts with Ni loading of 7% were prepared using the citric acid-assisted incipient wetness impregnation method. The authors found that the Ni particle size estimated by H 2 pulse chemisorption was in the range of 7.3-8.2 nm, which is dependent on the concentration of the citric acid used.…”
Section: Structural Properties and Crystal Size Of Reduced Ni-based C...mentioning
confidence: 99%
“…As per the IUPAC classification of isotherms, it is noteworthy that all catalysts exhibited type IV isotherms accompanied by H4 hysteresis loops. These characteristics indicate the predominance of mesopores and slit-like pores, respectively. Table provides insights into the surface area, revealing a substantial increase in the acid-activated SEP catalysts coupled with a modest enhancement in the pore volume. This observation underscores the efficacy of acid treatment in augmenting porosity.…”
Section: Resultsmentioning
confidence: 98%
“…24 Waris and Zhang et al also proposed that smaller Ni particles were found on SBA-15 by introducing citric acid through the impregnation method. 25,26 Until now, however, the noble metal loaded on the citric acid-assisted transition metal oxides/SiO 2 and their catalytic activity in the presence of H 2 O have not been reported. Moreover, the effect of citric acid on the electron transport property through the chemical bond interaction may play a key role in the catalytic activity in the presence of H 2 O, of which the method and mechanism also remain unclear.…”
Section: Introductionmentioning
confidence: 99%